Alzheimer Disease and Type 2 Diabetes Mellitus: The Link to Tyrosine Hydroxylase and Probable Nutritional Strategies - Aliev, Gjumrakch; Shahida, Khan; Hua Gan, Siew; Firoz, CK; Khan, Aziz; M. Abuzenadah, Adel; Kamal, Warda; A. Kamal, Mohammad; Tan, Yi; Qu, Xianqin; Reale, Marcella (CNS & Neurological Disorders - Drug Targets, 2014)
Alzheimer disease (AD) and type 2 diabetes mellitus (T2DM) are chronic health disorders that affect millions of people around the world. According to recent studies, there are molecular similarities in the inflammatory pathways involved in both AD and T2DM, which opens a new avenue for researchers with different perspectives to target the cause of these diseases rather than their obvious symptoms. Several links between inflammation, cardiovascular disease, T2DM and central nervous system disorders such as AD and Parkinson’s disease have been elucidated. Mutations in the hippocampal-β-amyloid precursor protein gene in genetically high-risk individuals have been shown to cause the early onset of AD symptoms. The overexpression of β-amyloid protein in the hippocampal region and the synaptotoxicity that occurs as a result have been considered a typical feature of AD and leads to neuronal loss and cognitive decline. However, the identity of the cellular components that cause the late onset of the disease seen in the majority of the cases is still unknown. Synaptic insults associated with neuronal dysfunction may involve several cascades and molecules, one of which has been hypothesized to be tyrosine hydroxylase (TH). The axons of the noradrenergic cells that project to the hippocampus appear to be affected by the β-amyloid protein, which subsequently contributes to TH loss in Alzheimer brain cells. In this review, we attempt to shed light on the important mechanisms involved in AD as well as T2DM such as inflammatory factors, abnormalities in the insulin signaling system and the possible role of the endocrine enzyme TH.
Keywords: Alzheimer disease